Chlorogenic acid improves growth performance of weaned rabbits via modulating the intestinal epithelium functions and intestinal microbiota - Chen, Jiali; Song, Zhicheng; Ji, Rongmei; Liu, Yongxu; Zhao, Hong; Liu, Lei; Li, Fuchang (Frontiers in Microbiology, 2022)
This study was conducted to investigate the impacts of chlorogenic acid (CGA) on growth performance, intestinal permeability, intestinal digestion and absorption-related enzyme activities, immune responses, antioxidant capacity and cecum microbial composition in weaned rabbits. One hundred and sixty weaned rabbits were allotted to four treatment groups and fed with a basal diet or a basal diet supplemented with 400, 800, or 1,600 mg/kg CGA, respectively. After a 35-d trial, rabbits on the 800 mg/kg CGA-supplemented group had higher (p < 0.05) ADG and lower (p < 0.05) F/G than those in control (CON) group. According to the result of growth performance, eight rabbits per group were randomly selected from the CON group and 800 mg/kg CGA group to collect serum, intestinal tissue samples and cecum chyme samples. Results showed that compared with the CON group, supplementation with 800 mg/kg CGA decreased (p < 0.05) levels of D-lactate, diamine oxidase, IL-1β, IL-6, and malondialdehyde (MDA), and increased IL-10 concentration in the serum; increased (p < 0.05) jejunal ratio of villus height to crypt depth, enhanced (p < 0.05) activities of maltase and sucrase, increased (p < 0.05) concentrations of IL-10, T-AOC, MHCII and transforming growth factor-α, and decreased (p < 0.05) levels of TNF-α and MDA in the jejunum of weaned rabbits. In addition, results of high-throughput sequencing showed that CGA supplementation elevated (p < 0.05) microbial diversity and richness, and increased (p < 0.05) the abundances of butyrate-producing bacteria (including genera V9D2013_group, Monoglobus, Papillibacter, UCG-005, and Ruminococcus). These results indicated that dietary supplementation with 800 mg/kg CGA could improve the growth performance of weaned rabbits by enhancing intestinal structural integrity, improving the intestinal epithelium functions, and modulating the composition and diversity of gut microbiota.